Lactose-decorated, alginate-coated chitosan nanoparticles loaded with Coomassie Brilliant Blue G-250 protect colonic barrier integrity in experimental colitis - Maha M. Amer; Ahmed Y. Kira; Sameh Saber; Abdulaziz A. Alsalloom; Mostafa M. Khodeir; Hala A. Elashry; Rabab S. Hamad; Adel Alhomaidi; Hamad Alsaykhan; Mohammed Alorini; Mohamed R. Abdel-Hamed; Huda Eltayeb; et al. (Tissue and Cell, 2026)

Functional roles of ginger (Zingiber officinale) in strengthening the physiological responses, growth, antioxidant/immune gene expression, and resistance to Fusarium oxysporum in Red Tilapia (Oreochromis sp.): in vivo and in silico approaches - Roshmon Thomas Mathew; Mohamed Ashour; Michelyne Haroun; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Hesham Abdallah Hassanien; Huda Ahmad Alamer; Hailah M. Almohaimeed; Ehab Faiyz Wahbah; Nashmiah S. Alshammari; Amal Ali Alharbi; et al. (Tropical Animal Health and Production, 2026)

Macromodeling and experimental investigation of RC frames infilled with clay bricks and autoclaved aerated concrete blocks under cyclic loading - Ahmed M. El-Kholy; Huda Sayed; Ibrahim M. Metwally; Ayman A. Shaheen (Bulletin of Earthquake Engineering, 2026)
This study investigates the cyclic behavior of reinforced concrete (RC) frames infilled with autoclaved aerated concrete (AAC) blocks—a novel and environmentally friendly material—compared to traditional clay masonry infill commonly used in Egypt. In addition, the RC frames were reinforced with an advanced type of reinforcing steel designed to enhance seismic resistance. Three 2/3-scale RC frames were experimentally tested under cyclic lateral loading. Both infill types contributed approximately equally to increasing the lateral strength of the RC frame (around 60% improvement); however, the AAC infill significantly outperformed the brittle clay infill in terms of ductility enhancement. To characterize the response, trilinear and quadlinear backbone curves were developed for the clay and AAC infills, respectively. Alongside the experimental work, numerical macromodeling of the infill panel as multi-strut and single-strut macromodels using SeismoStruct and SAP2000, respectively, was conducted. Additionally, both concentrated and distributed plasticity approaches were employed to model the nonlinear behavior of the RC elements. A suitable constitutive steel model was used to numerically track the experimental hysteresis response of the steel reinforcement. The multi-strut macromodel demonstrated superior accuracy in capturing the hysteresis behavior of the infilled RC frames compared to the single-strut model. The strut width and its post-cracking degradation rate, the shear-to-axial stiffness ratio, and the strain in the infill at peak stress were key parameters influencing the accuracy of the complex multi-strut macromodel in distinguishing between the brittle behavior of clay infill and the ductile response of AAC infill.

Dietary co-supplementation of Pediococcus acidilactici and bergamot essential oil improves growth, immune response, and disease resistance in sea bream (Sparus aurata) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Hesham Abdallah Hassanien; Abdullah Sheikh; Huda Ahmad Alamer; Hailah M. Almohaimeed; Ehab El-Haroun; El-Sayed Hemdan Eissa; Sameh A. Abdelnour (Aquaculture International, 2025)

Histopathological, immunohistochemical, and molecular investigation of atrazine toxic effect on some organs of adult male albino rats with a screening of Acacia nilotica as a protective trial - Zainab Sabry Othman Ahmed; Mohamed Abdelaziz Tahon; Randa S. Hasan; Hazem G. M. El-Sayed; Huda O. AbuBaker; Ismaiel M. Ahmed; Yasmine H. Ahmed (Environmental Science and Pollution Research, 2022)

Co-inheritance of alpha globin gene deletion lowering serum iron level in female beta thalassemia patients - Sayed AbdulAzeez; Noor B. Almandil; Zaki A. Naserullah; Sana Al-Jarrash; Ahmed M. Al-Suliman; Huda I. ElFakharay; J. Francis Borgio (Molecular Biology Reports, 2020)

Erratum to: Haemopoiesis in the head kidney of tilapia, Oreochromis niloticus (Teleostei: Cichlidae): a morphological (optical and ultrastructural) study - El-Saydah H. Abdel-Aziz; Suzan B. S. Abdu; T. El-Sayed Ali; Huda F. Fouad (Fish Physiology and Biochemistry, 2012)

Haemopoiesis in the head kidney of tilapia, Oreochromis niloticus (Teleostei: Cichlidae): a morphological (optical and ultrastructural) study - El-Saydah H. Abdel-Aziz; Suzan B. S. Abdu; Tamer El-Sayed Ali; Huda F. Fouad (Fish Physiology and Biochemistry, 2010)